Acceptance and needs of medication literacy education among children by their caregivers: A multicenter study in mainland China - Xu, Xiaolin; Wang, Zhonglan; Li, Xialei; Li, Ying; Wang, Yu; Wu, Xuexin; Hao, Lina; Wang, Xiaoling (Frontiers in Pharmacology, 2022)
Background: This study aims to investigate the needs of child caregivers for popular science about safe medication for children, to deeply explore the characteristics of child caregivers’ demand for safe medication and the shortcomings of current popular science work, and then to seek better coping strategies to ensure children’s safe medication. Methods: A questionnaire was designed based on Lasswell’s “5W” communication model to investigate the needs of child caregivers in terms of content, channels, and forms of popular healthcare science on the safe usage of children’s medication. Results: The primary ways caregivers receive popular healthcare science education concerning safe medication usage knowledge are through medical institutions, notification by medical staff, and personal media. The caregivers of children have a high demand for the presentation of text, pictures, and videos in three forms of popular healthcare science content. Caregivers placed significant importance on the popularization of safe medication usage for children. The survey results showed that the top 3 ways for caregivers to think that the quality of popular healthcare science content was “very good” came from medical institutions, medical staff notifications, and personal media, effectively increasing popular healthcare information accuracy. The intelligibility and pertinence of content expression are urgently needed within the caregiver population. Conclusion: Caregivers are very concerned about the popular science of safe medication for children, and are willing to learn about relevant content. Guided by the demand, we should actively disseminate accurate and easy-to-understand popular science about safe medication for children to caregivers through online or offline channels so as to promote safe medication for children.